If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/5(x-4)-1/3(2x-9)=1/4
We move all terms to the left:
3/5(x-4)-1/3(2x-9)-(1/4)=0
Domain of the equation: 5(x-4)!=0
x∈R
Domain of the equation: 3(2x-9)!=0We add all the numbers together, and all the variables
x∈R
3/5(x-4)-1/3(2x-9)-(+1/4)=0
We get rid of parentheses
3/5(x-4)-1/3(2x-9)-1/4=0
We calculate fractions
(36x2/(5(x-4)*3(2x-9)*4)+(-20xx/(5(x-4)*3(2x-9)*4)+(-15x^2x/(5(x-4)*3(2x-9)*4)=0
We calculate terms in parentheses: +(36x2/(5(x-4)*3(2x-9)*4)+(-20xx/(5(x-4)*3(2x-9)*4)+(-15x^2x/(5(x-4)*3(2x-9)*4), so:
36x2/(5(x-4)*3(2x-9)*4)+(-20xx/(5(x-4)*3(2x-9)*4)+(-15x^2x/(5(x-4)*3(2x-9)*4
We can not solve this equation
See similar equations:
| -2.5=0.75z+0.5 | | 100(2(5x+4x)=36000 | | 5a-3=3a–5 | | 3x^2+138x-1260=0 | | x+0.05x=779.10 | | 21/x+9=7/8 | | 4(x-5)=7x+20 | | 2z/3+7=9+z | | (x-5)^2=72 | | 8x+12=x-2 | | 3x+29=4x+35 | | 15y+9=2y-12 | | 3m-5=20m | | 6(2j-4)+4(4j-3)=20 | | 0=30-5(m-6) | | 4v2-5v=v | | 4t-20=6t+3 | | 4b2-10b=-b2-5 | | 3m+1=180 | | 9+22x=5 | | 21=30+p | | -6x+8(x-3)=-26 | | 7r2=-1+8r | | 1/3x=208 | | 4y-2(5+3y)=25 | | 1/3x+x=208 | | 7(x-2)=-11 | | 6x2=7x-1 | | 6=30(x)^25 | | 0.7(y+–2.2)+–3.9=–6.49 | | -9v-4v=-2v+9 | | 16x^2+2x−3=0 |